Employee Net Promoter Score Impact on Measuring Employees’ Experience and On Shaping Employer Branding Strategy: Empirical Research in Poland - Dorota KUREK (Communications of International Proceedings, 2022)
Measuring employee experience as an important source of information requires the selection of appropriate tools, including indicators that, when studied regularly, allow for a better understanding of employees and to assess the effectiveness of commission activities. In the literature on the subject, the issue of using the Employee Net Promoter Score is not sufficiently described, which prompted the author to fill the gap in this area and show how the indicated tool can be used in practice in order to obtain the necessary information in the process of building the image of the organization as an employer. The main purpose of the article is to show how organisation can use the Net Promoter Score indicator adapted to the needs of implementing image-promoting activities. The article presents the results of a survey conducted in Poland in 2022 on a sample of 384 working people. While presenting the results in terms of ENPS, attention was also paid to the generational and gender diversity of employees, as two key variables that can affect the ENPS indicator. Based on the conducted research, it was determined how many employees in Poland declare a positive image of their employer as an organisation on the market, and how many respondents rate their work experience positively. It was established that the ENPS indicator was only -7.55, which indicates the need for further activities in the field of building the image of the organization in Poland.
Keywords: ENPS; employee experience; EB strategy; KPIs; organisational image.